The Effectiveness of Inquiry Worksheet with Pair Checks Approach to Improve Learning Outcomes and Scientific Attitudes - Ni'mah, Nailin; Wardani, Sri (Journal of Environmental and Science Education, 2021)
Learning outcomes are important to form intelligent and skilled humans. This study aims to determine the effectiveness of inquiry worksheet with pair checks approach to improve learning outcomes in the cognitive domains and scientific attitudes. The research design used was an experimental control group with pretest-posttest. The research population was eighth grade in SMP N 1 Semarang. The research sample was taken using a simple random sampling technique. This research applies an inquiry worksheet with a pair checks approach for experimental classes and regular worksheet for control classes. The significance test of learning outcomes in the cognitive domain shows differences in learning outcomes for the two samples. The N-Gain value measured the increase in learning outcomes in the cognitive domain. The N-Gain value for the experimental class was 0.39, which was in the moderate category. The N-Gain value for the control class is 0.27 which was in the low category. The result of the observation shows that the inquiry worksheet with the pair checks approach is not effective in improving scientific attitudes. Students' scientific attitude has decreased for every meeting because of constraints for online learning as a result of the pandemic Covid-19. The student response to the application of the inquiry worksheet with the pair checks approach was 82.21% which was in the very good category.